Los diplomáticos mexicanos durante la Revolución: entre el desempleo y el exilio - Rosenzweig, Gabriel (El Colegio de México, A.C., 2012)
In August 1914, Venustiano Carranza, in his role of first commander in chief of the constitutionalist army in charge of the executive power, decreed the cessation of the members of the Mexican foreign service. This paper seeks to explain the way in which such a decree was applied; what happened to the diplomats, particularly regarding their struggle for subsistence and their political activities; and, last but not least, their reconciliation with the revolution. It also examines the degree to which this group was part of the exile of the revolution. The analysis is based on the ranking of January 1st, 1914 and the files of the foreign service members, kept in the Genaro Estrada Archive of the Ministry of Foreign Affairs.